The Centrality of "Santi" in Hindu Scriptures - Thannippara, Alexander (Journal of Dharma, 1986)
Even a casual visitor to India will be struck by the devotional songs and bhajans comig through the loud-speakers of a temple early in the morning. If he pays a little attention, it may be possible for him to decipher a few syllables, which are repeated again and again: "Öm, šãnti, šänti, šänti", i.e., "0m, peace, peace, peace', Yes, our Hindu neighbour is beginning his day with the chanting of 'Šänti-mantra' the prayer for peace. He is praying for order, harmony and peace in this world and also for the eternal and everlasting peace in the world to come. Without any exaggeration we can say that a devout Hindu will not only be beginning his day with the 'Sänti mantra' but will also be repeating the same several times every day.